Studying Green Purchase Behavior Of Malaysian Consumers - Camare, Hooman Mostofi (2008)
This study has used theory of planned behaviour to study green purchase behaviour of Malaysian consumer. This theory uses perceived consumer effectiveness, arritudes and subjective norms as predisctors of behavioural intention.